1997
DOI: 10.1002/(sici)1098-2795(199711)48:3<301::aid-mrd1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y binds to the CCAAT box motif of the FGF-4 gene and promotes FGF-4 expression in embryonal carcinoma cells

Abstract: FGF‐4 appears to be the first fibroblast growth factor (FGF) expressed during embryogenesis, and its expression is critical for early mammalian development. FGF‐4 is expressed in the embryonic cell lines, F9, D3, and NT2/D1; but its expression in these cells is repressed upon differentiation. Transcription of the FGF‐4 gene in embryonic cells is regulated by an enhancer in the third exon and by a positive regulatory region upstream of the transcription start site. A CCAAT box motif within the positive regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…6B). Various other authors have also observed a decrease in promoter activity of the target gene upon co-expression with the dominant-negative NF-YA mutant (Lamb et al, 1997; Liu et al, 1997; Sugiura and Takishima, 2000; Kam et al, 2005; Wageningen et al, 2008). …”
Section: Discussionmentioning
confidence: 93%
“…6B). Various other authors have also observed a decrease in promoter activity of the target gene upon co-expression with the dominant-negative NF-YA mutant (Lamb et al, 1997; Liu et al, 1997; Sugiura and Takishima, 2000; Kam et al, 2005; Wageningen et al, 2008). …”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the FGF-4, TβR-II, and CYP1A1 genes each contain identical CCAAT box-like sequence motifs in each of their respective promoters (5′-TGATTGGCAG-3′). Unlike the Sox-2 CCAAT box motif, gel mobility shift analysis of the FGF-4, TβR-II, and CYP1A1 CCAAT box motifs revealed formation of two distinct DNA/protein complexes, one of which contains NF-Y (Boucher et al, 1993(Boucher et al, , 1995Lamb et al, 1997;Kelly et al, 1998). Both complexes are specific for the CCAAT box-like motif, as an unlabeled FGF-4, TβR-II, or CYP1A1 mutant CCAAT box competitor, in which only the CCAAT box has been scrambled, does not compete for either complex (Kelly and Rizzino, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…These genes all contain the sequence (5′-TGATTGGC AG-3′), which differs by only one base pair (underlined) with the Sox-2 CCAAT box (5′-TGATTGGCCG-3′). Previous gel mobility shift assays demonstrated that the CCAAT box motif from each of these three genes can form two DNA/protein complexes, one of which contains NF-Y (Boucher et al, 1993(Boucher et al, , 1995Lamb et al, 1997;Kelly et al, 1998). To determine whether NF-Y binds the Sox-2 CCAAT box motif, we performed gel mobility shift analysis using a dsODN probe containing the CCAAT box sequence of the Sox-2 promoter.…”
Section: Role Of a Consensus Ccaat Box Motif Present In The Sox-2 Promentioning
confidence: 99%
“…NF-Y was originally identified as a ubiquitously expressed protein that binds to the Y box motif, originally defined as an inverted CCAAT box motif (CTGATTGGYY) in all MHC class II genes that is critical for tissue specific gene expression (71). Although the exact mechanism(s) by which NF-Y regulates transcription is unclear, it has been demonstrated to act as both a positive (66,72,73) and a negative (74) transcription factor. Several studies suggest that NF-Y acts by stabilizing or recruiting the binding of additional factors to adjacent promoter elements (75,76).…”
Section: Nf-y Influences T␤r-ii Expression Inmentioning
confidence: 99%